Efforts to Increase the Effectiveness of Teacher Performance in the Learning Process Through Academic Supervision with a Collaborative Approach - Runtifasih, Runtifasih (Indonesian Journal of Educational Science and Technology, 2023)
The aim of this research is to get an empirical picture of how teachers improve their performance in learning through academic supervision with a collaborative approach for teachers at SD Negeri Temanggal, Adimulyo District, Kebumen Regency in semester 2 of the 2022/2023 school year. This research uses School Action Research or School Action Research to see how teachers carry out learning in semester 2 of the 2022/2023 academic year at SD Negeri Temanggal, Adimulyo District, Kebumen Regency. Using Miles and Humberman's interactive model, data analysis was carried out in four stages: (1) data collection and review; (2) comparative description; (3) data presentation; and (4) draw verification of conclusions. Important findings in this research are: 1). Teacher performance continues to improve after academic supervision is carried out. 2). Academic supervision with a collaborative approach can increase learning effectiveness for teachers at SD Negeri Temanggal, Adimulyo District, Kebumen Regency.